MANAJEMEN ASUHAN EBIDANAN REMAJA PADA Nn “S” DENGAN DISMINORHEA PRIMER DI POLI KEBIDANAN DAN KANDUNGAN RS ISLAM FAISAL MAKASSAR TAHUN 2021 - Risky Amelia; Ferawati Taherong; Andi Dian Diarfah (Jurnal Midwifery, 2022)
Introduction Adolescence is a period of individual life in which psychological exploration occurs to determine self-identity. During adolescence, physical changes would also occur, in which menstruation becomes the most notice worthy element. The problem that is often experienced by women during menstruation is discomfort or severe pain. The pain that arises is known as dysmenorrhea, which consists of two categories, namely primary dysmenorrhea and secondary dysmenorrhea. The most common one is the primary dysmenorrhea, including experiencing severe pain which may interfere daily activities. This research aims to investigate adolescent midwifery care management on Ms. “S” with primary dysmenorrhea at Obstetrics and Gynecology Polyclinic -RSI Faisal Makassar from August 20th to September 21st 202 using Helen Varney’s 7-step midwifery care management approach and house-visit SOAP technique. The result of this research states that adolescents with Primary Dysminorhea, aged 18 years, complained of abdominal pain experienced for 2 days, nausea and vomiting more than 4 times, weakness and respiratory problems, tender breasts and abdominal tenderness and tension. However, ultrasound examination showed no abnormalities. Conclusion The treatment was conducted by giving infusions, drugs and oxygen. It can be concluded that current physical examination on Ms."S" shows abdominal pain happened for 2 days, nausea and vomiting, weakness and a little shortness of breath. Physical examination also states that there is a pain in the breasts and abdomen. It is also obvious from the treatment result that there are no more complications and stomach pain felt by the patient. Midwives as health workers are expected to provide care for adolescents with primary dysmenorrhea by providing understanding or explanation, appropriate preventive treatment and Islamic therapy to reduce the stress of the patients.